Personal, social and environmental correlates of vegetable intake in normal weight and overweight 9 to 13-year old boys - Thorsdottir Inga; Rasmussen Mette; Klepp Knut-Inge; te Velde Saskia J; Yngve Agneta; De Bourdeaudhuij Ilse; Wolf Alexandra; Brug Johannes (BMC, 2006)
Abstract Background The first aim of the present study was to investigate differences in correlates of vegetable intake between the normal weight and the overweight boys in the Pro Children Cross Sectional Study. The second aim was to explore whether the association between vegetable intake and potential correlates is different in overweight boys compared with normal weight boys. Methods Random samples of mainly 11-year old children were recruited in 9 European countries. The total sample size consisted of 3960 boys (16.5% overweight). A validated self-report questionnaire was used to measure vegetable intake, and personal, social and environmental factors related to vegetable intake in the classroom. Weight and height were reported by the parents of the children in parents' questionnaires. Results Regression analyses explained 23% to 28% of the variance in vegetable intake by potential correlates. Liking, self-efficacy and bringing vegetables to school were related to intake in both normal weight and overweight boys (β's>0.10). Active parental encouragement and availability at home was only related to intake in overweight boys (β's>0.10), whereas knowledge about recommendations was only related to vegetable consumption in normal weight boys (β>0.10) Conclusion Intervention strategies to increase vegetable intake should focus on increase in liking and preferences, increase in self-efficacy, and increase in bringing vegetables to school in both normal weight and overweight boys. Further research should investigate whether advising parents of overweight boys to encourage their child to eat vegetables every day, to insist as far as possible that their child eats vegetables regularly and to make vegetables easily available at home is effective in changing vegetable intake.